Flare minimisation via dynamic simulation. (16th March 2007) - Singh, Amarnath; Li, Kuyen; Lou, Helen H.; Hopper, J.R.; Golwala, Hardik; Ghumare, Sandesh; Kelly, Thomas
This paper describes a project of flare minimisation during plant startup by using dynamic simulation. Dynamic simulation was developed for recovery area in an olefin plant and used to examine startup procedures: approaching shutdown; startup with recycle ethane; starting the cracked feed and increasing the feed to normal production rate. The dynamic simulation gives an insight into the process dynamic behaviour that is not apparent through the use of steady state simulation. This information is crucial for plant startup in order to minimise the flaring. This project demonstrated a feasibility of pollution prevention through flare minimisation for an olefin plant.